Histological alterations of gallbladder mucosa and selected clinical data in young patients with symptomatic gallstones - Kasprzak, Aldona; Malkowski, Wojciech; Biczysko, Wiesława; Seraszek, Agnieszka; Sterzyńska, Karolina; Zabel, Maciej (Polish Journal of Pathology, 2011)
Department of Histology and Embryology, University of Medical Sciences, Poznań Histological lesions of gallbladder were described mainly in older patients with cholelithiasis (CH). The aim of the study was to analyse morphological alterations in gallbladder mucosa and selected clinical data of young patients with CH. The studies were conducted on 57 patients with CH, subjected to cholecystectomy in the years of 2003-2007. In course of the years, 37 respective young patients (below 25 years of age) were operated. The comparative group included twenty 50-year-old patients with gallstones. The inflammatory activity (grading) was evaluated using a semiquantitative scale on HE-stained gallbladders. In either group, women with chronic cholecystitis and multiple gallstones prevailed. Histological alterations in young patients involved absence of evident epithelial metaplasia traits, low number of foamy cells and prevalence of eosinophils in gallbladder mucosa. Even if a similar grading in gallbladder walls was noted in young and older patients, only in the former ones, a higher grading was detected in patients with an acute clinical course of the gallstone disease. The results point also to a potential role of local accumulation of eosinophils in gallbladder mucosa in pathogenesis of CH in young patients.